Phase separation dynamics and morphologies prediction of PEO-b-PMMA copolymer by atomistic and mesoscopic simulations - Chiangraeng, Natthiti; Lee, Vannajan Sanghiran; Nimmanpipug, Piyarat (The Committee on Publication Ethics, 2018)
Atomistic and mesoscopic simulations are the most important tools to predict the morphologies of block copolymers. In this study, inter-bead interactions and essential parameters for meso-structure polymeric models were optimized for poly(ethylene oxide)-block-poly(methyl methacrylate) (PEO-b-PMMA; O-b-M) binary systems. A coarse-grained model in a mesoscopic dynamic was used to represent polymeric chain. Gaussian chain is calculated from polymer chain length concerning its characteristic properties. Free energy density was considered by setting suitable time steps and inter-bead interactions for meso-structure simulations. The interaction energies of 1:1, 2:1 and 4:1 molar ratio of O to M segments were 3.67, 4.66, and 5.92, respectively. These values are obtained from Flory-Huggins parameters in atomistic simulations. Morphology at equilibrium was obtained in five different types: worm-like micelle, defected lamellar, lamellar, spherical micelle and bicontinuous at 400 K from M5-1M2-O5, O4-O4M6, M4-M5O5, O10-2M122-O10 and M11-1M2-O10, respectively. The obtained morphologies correlate with order parameter developed from the simulations.